Tackling malignant melanoma epigenetically: histone lysine methylation - Elias Orouji; Jochen Utikal (Clinical Epigenetics, 2018)
Abstract Post-translational histone modifications such as acetylation and methylation can affect gene expression. Histone acetylation is commonly associated with activation of gene expression whereas histone methylation is linked to either activation or repression of gene expression. Depending on the site of histone modification, several histone marks can be present throughout the genome. A combination of these histone marks can shape global chromatin architecture, and changes in patterns of marks can affect the transcriptomic landscape. Alterations in several histone marks are associated with different types of cancers, and these alterations are distinct from marks found in original normal tissues. Therefore, it is hypothesized that patterns of histone marks can change during the process of tumorigenesis. This review focuses on histone methylation changes (both removal and addition of methyl groups) in malignant melanoma, a deadly skin cancer, and the implications of specific inhibitors of these modifications as a combinatorial therapeutic approach.